Pengaruh Kesadaran Merek Terhadap Niat Beli Dengan Sikap Rekomendasi Sponsor Sebagai Variabel Mediasi Pada Konsumen Samsung di Kota Banda Aceh - Iskandarsyah Madjid; Adek Maulana (Faculty of Economics and Business, Universitas Malikussaleh, 2016)
The purpose of this study was to measure the impact of brand awreness to purchase intention with attitude toward sponsor recomendation as mediating variables on Phone cell consumers in Banda Aceh. Data we collected from a sample of 100 respondents. Data collection equipments used in this research is a questionnaire. The sampling technique used was purposive sampling. Hierarchical Linear Modeling (HLM) was used as method of analysis to determine the effect of all the variablesinvolved. Based on the result of HLM analysis there is a positive effect on brand awareness toward purchase inten, brand awareness has a positive influence on the sponsor recommendation behavior, sponsor recommendation behavior has a poitive influence on purchase intentions, and attitude toward sponsor recomendation mediated the effect of the brand awareness toward purchase intention.Keywords: Brand Awareness, Attitude Toward Sponsor Recomendation, PurchaseIntention, Hierarchical Linear Modelling